2013
DOI: 10.7860/jcdr/2013/4491.2757
|View full text |Cite
|
Sign up to set email alerts
|

The Corpus Callosum Wallerian Degeneration in the Unilateral Brain Tumors: Evaluation with Diffusion Tensor Imaging (DTI)

Abstract: Purpose: The purpose of this study was to evaluate whether DTI could demonstrate the water diffusivity changes in the corpus callosum (CC), which were not visible on the morphologic imaging in patients with glioblastoma multiforme (GBM) and brain metastases with no midline CC infiltration. Materials and Methods:Twenty-seven patients with treatment naïve unilateral GBM and eleven patients with a solitary brain metastasis with no midline CC infiltration underwent DTI. Ten controls with normal brain MRI were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 19 publications
(31 reference statements)
0
29
0
Order By: Relevance
“…For example, a previous histopathological study on postmortem brains showed that nerve fibers from inferior frontal and anterior inferior parietal regions course through the rostrum and genu, the fibers from superior frontal and anterior parietal regions course through the anterior two‐thirds of the body, and fibers from temporo‐parieto‐occipital regions course through the splenium and caudal body . In the last decade, DTI has revealed changes in the CC remote from the site of injury in the setting of cerebral infarction, tumor, epilepsy, and others . In a previous study, we demonstrated that DTI measurements from the CC not only can quantify tumor infiltration in patients with glioblastoma but can also predict overall survival .…”
Section: Corpus Callosummentioning
confidence: 80%
“…For example, a previous histopathological study on postmortem brains showed that nerve fibers from inferior frontal and anterior inferior parietal regions course through the rostrum and genu, the fibers from superior frontal and anterior parietal regions course through the anterior two‐thirds of the body, and fibers from temporo‐parieto‐occipital regions course through the splenium and caudal body . In the last decade, DTI has revealed changes in the CC remote from the site of injury in the setting of cerebral infarction, tumor, epilepsy, and others . In a previous study, we demonstrated that DTI measurements from the CC not only can quantify tumor infiltration in patients with glioblastoma but can also predict overall survival .…”
Section: Corpus Callosummentioning
confidence: 80%
“…The causes and time course of remote degeneration have been studied in many diseases (including stroke) via experimental procedures, pathology studies, and neuroimaging. 16 Knowledge of how disconnection caused by remote degeneration affects distant brain regions may be important, because losses in white matter (WM) integrity have been associated with functional deficits, including motor recovery after stroke. 3,7,8 Therefore, it may be helpful for clinicians to be able to predict which regions are susceptible to remote degeneration as it could enhance their prognostic abilities and enable more focused and individualized rehabilitative strategies.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, WD showed a limited increase in diffusivity as there was neither formation of cysts nor significant water accumulation in the interstitial space. Studies have demonstrated WD in CC in brain tumors patients where tumors do not infiltrate the CC (48). Another imaging study of temporal lobe epilepsy showed changes not only in the seizure site, but also in remote locations such as the splenium of CC owing to secondary WD-mediated white matter degeneration (49).…”
Section: Discussionmentioning
confidence: 99%